Pengaruh Model Problem Based Learning Berbantuan Media Powerpoint terhadap Hasil Belajar IPAS Siswa Kelas V Sekolah Dasar Negeri 39 Pontianak Kota - Dita Areska; Herry Kresnadi; Asmayani Salimi (Departement of Mathematics Education, 2024)
This research aims to determine whether or not there is an influence and how much influence the Problem Based Learning model assisted by PowerPoint media has on the science and science learning outcomes of class V students at SDN 39 Pontianak Kota. The research method used is experimental with a quantitative type of research. The data source for this research is fifth grade students at SDN 39 Pontianak City and the data is a pre-test and post-test multiple choice question sheet on environmental problems that threaten life. The results of the research show that the use of the Problem Based Learning model assisted by PowerPoint media has an effect on student learning outcomes with calculated values based on hypothesis testing (Independent Samples T-test). The t-count value is = 11.303 and the t-table value is = 2.05, so Ho is rejected and Ha accepted. Thus, it can be concluded that there is an influence of the Problem based Learning model assisted by PowerPoint media on the science and science learning outcomes of class V students at SDN 39 Pontianak Kota, while the effect size calculation results are 0.49 and fall into the medium category.